2016
DOI: 10.1155/2016/6805169
|View full text |Cite
|
Sign up to set email alerts
|

Acute Kidney Injury Classified by Serum Creatinine and Urine Output in Critically Ill Cancer Patients

Abstract: Acute kidney injury (AKI) is common in critically ill patients and is associated with higher mortality. Cancer patients are at an increased risk of AKI. Our objective was to determine the incidence of AKI in our critically ill cancer patients, using the criteria of serum creatinine (SCr) and urine output (UO) proposed by the Kidney Disease: Improving Global Outcomes (KDIGO). Methods. We performed a retrospective cohort analysis of a prospectively collected database at the intensive care unit (ICU) of the Insti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Moreover, these are also the chronic conditions that frequently increase morbidity and mortality for AKI in critically ill patients who are septic, 11,16,25 with fluid overload, 2,9,26 making use of nephrotoxic drugs 16 or who have undergone major surgeries. 7,8 Other chronic pathological conditions that are also noted as risk factors for AKI incidence and mortality in critically ill patients include cardiovascular, 9,17,27-30 respiratory, 10,31 cerebrovascular, 16 cirrhosis, 32,33 cancer 15,25 , and human immunodeficiency virus infection. 10,34 Several studies have shown baseline renal function as one of the most important risk factors for AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these are also the chronic conditions that frequently increase morbidity and mortality for AKI in critically ill patients who are septic, 11,16,25 with fluid overload, 2,9,26 making use of nephrotoxic drugs 16 or who have undergone major surgeries. 7,8 Other chronic pathological conditions that are also noted as risk factors for AKI incidence and mortality in critically ill patients include cardiovascular, 9,17,27-30 respiratory, 10,31 cerebrovascular, 16 cirrhosis, 32,33 cancer 15,25 , and human immunodeficiency virus infection. 10,34 Several studies have shown baseline renal function as one of the most important risk factors for AKI.…”
Section: Discussionmentioning
confidence: 99%
“…AKI was defined according to the KDIGO definition. 7 As per 2011 Renal Association guidelines, 9 and recent articles, [22][23][24][25] baseline creatinine was defined as the lowest creatinine level recorded within 3 months. If a 3-month creatinine was not available, then AKI was not diagnosed, assuming other criteria were not met.…”
Section: Resultsmentioning
confidence: 99%
“…From their large database, Kellum et al reported that 59% of ICU patients with acute kidney injury (AKI) met the KDIGO urine output criteria [8]. In a smaller cohort, Md Ralib et al reported that 61% of patients with AKI met urine output criteria (< 0.5 ml/kg/h) [11], and in a study of critically ill cancer patients, 56% met urine output criteria for AKI [18]. The mortality rate was higher in patients with oliguria than in those without.…”
Section: Discussionmentioning
confidence: 99%